University journalism education. Mere technological training or comprehensive education in the new information environment? - García Santamaría, José Vicente; Barranquero Carretero, Alejandro (Historia y Comunicación Social, 2014)
This paper approaches the main challenges of university journalism education facing a new labour market defined by the permanent changes brought about by digitalization. The methodology is based both on an extensive review of referential academic literature and on the first results of a qualitative research on new business models in the digital press, from which we define the most demanded professional profile.
Keywords: journalism education; digitalization; convergence; online journalism.